St. Lucia Technical Assistance Report-Rebasing GDP Mission. (IMF Staff Country Reports; Country Report ;, 2020)
A technical assistance mission was undertaken by the Real Sector Statistics Advisor in the Caribbean Regional Technical Assistance Centre to Saint Lucia to provide advice to the Central Statistics Office (CSO) on compiling rebased gross domestic product estimates. The CSO is responding to the needs of the Ministry of Finance for more robust and timely national accounts statistics. All the Gross domestic product by economic activity (GDP-P) compilation workbooks have now been redeveloped and revised current and constant 2018 price quarterly and annual estimates have been compiled up to Q3 2019. The incorporation of revised data on tourist expenditure for 2000 onward have also resulted in revisions to the GDP-P current rice estimates and real growth rates. The revised annual and quarterly GDP-P estimates were assessed, and several methodological improvements were implemented. Improvements were made to the constant price estimates by reviewing and replacing weaker volume indicators. Training on the methodological changes and compiling the rebased estimates has been provided. The training on methodological improvements included the use of the more representative employment indicators and various price indices discussed above; back-casting and linking techniques for the current price estimates and linking the constant 2006 price series with the constant 2018 price series.